A Guide to Government in Afghanistan - Evans, Anne (Washington, DC: World Bank, 2013)
This guide has three objectives: First and foremost, it seeks to provide newcomers to the Administrative and political scene in Afghanistan with a basic guide to the structures and processes of government. Second and related, it intends to provide reformers with some understanding of how to work "with the grain" of the existing institutional arrangements. Third, this report seeks to pay tribute to the remarkable people who have kept the system running and who are now reforming it. In pursuing these objectives, this guide attempts to set out these underlying strengths of the public sector, describing the evolution of the Afghan state, the current political context, and the administrative and organizational components of the government. It sets out the legal basis and organizational responsibilities for key fiscal tasks including revenue collection, budget preparation and execution, and accounting and audit. It also describes the organizational structures in the provinces, the way in which the staffing establishment is determined, and the structure of pay and grading. In particular, it looks at the arrangements for service delivery in the education and health sectors. A companion paper, "Subnational Administration in Afghanistan : Assessment and Recommendations for Action," (report no. 29415) outlines some specific recommendations resulting from these studies.